Teaching in today's inclusive classrooms : a universal design for learning approach - Gargiulo, Richard M.; Metcalf, Deborah J. (Belmont, CA : Wadsworth Cengage Learning, 2013)
Teaching in today's inclusive classrooms is a concise, accessible, and current main text for the Introduction to Inclusive Teaching course. It is the only inclusion textbook available with a consistent, integrated emphasis on Universal Design for Learning (UDL)--an important, contemporary educational philosophy focused on using strategies and tools to help ALL students by accommodating their differences. This text also provides foundational information about children with disabilities who are included in today's classrooms, and the most effective strategies for teaching them alongside their typically developing peers. Featuring new case studies and sound research-based teaching and learning strategies, this hands-on text offers pre-service and in-service teachers a practical, flexible framework for effective instruction, classroom management, assessment, and collaboration in today's diverse classrooms. -- Publisher.
Part 1. Foundations for educating all learners -- Part 2. Planning instruction for all learners -- Part 3. Implementing effective instructional practices for all learners.
Includes bibliographical references (p. 475-495) and index.
Keywords: Inclusive education -- United States -- Textbooks; Teaching -- United States -- Textbooks